Ethnicity and tone production on Singlish particles - Soh, Ying Qi (2023)
Recent research on Singlish, also known as Colloquial Singapore English, suggests that it is subject to ethnic variation across the three major ethnic groups in Singapore, namely Chinese, Malay, and Indian. Discourse particles, said to be one of the most distinctive features of the language, are nevertheless commonly used by bilinguals across all three ethnic groups. This study seeks to determine whether there are ethnic differences in the pitch contours of Singlish discourse particles produced by Singlish speakers. Four hundred and forty-four tokens of three Singlish particles, sia24, meh55, and what21, produced by the three groups of English-speaking bilingual speakers were drawn from the National Speech Corpus, and the pitch contours extracted and normalized. Statistical analysis of the overall pitch contours, the three acoustic parameters of mean pitch, pitch range, and pitch movement, and the variability of these parameters showed that the effect of ethnicity on the three acoustic parameters was not statistically significant and that the pitch contours of each particle were generally similar across ethnic groups. The results of this study suggest that Singlish may be acquired as a first language by Singaporean speakers, pre-empting any ethnic differences in the production of the particles that might otherwise have resulted from the speakers’ differing language repertoires.